Challenges to Diplomatic Efforts in Resolving Nepal-India Border Problems in the Himalayas: A Foreign Policy Analysis (FPA) - Bhattarai, Gaurav (Nepal Public Policy Review, 2021)
The Constitutional Provision on Nepal’s Foreign Policy has emphasized securing Nepal’s international borders. Nepal’s Foreign Policy-2077 also demands Nepal’s border to be kept intact by protecting international border points and resolving boundary issues via the means of peaceful diplomatic negotiations and dialogues, based on historic documents, treaties, agreements, facts and evidence. Despite the constitutional provision and foreign policy directives, Nepal’s border problems with its Southern neighbour remain unresolved. Despite having friendly bilateral relations, and cross-border civilizational linkages, Nepal-India relations are not free from border problems. Even during the pandemic, when both countries closed their borders to contain the spread of the coronavirus, they resorted to border confrontations taking the bilateral relations into the low ebb. This study examines the border problems between Nepal and India during the time of COVID-19 with a focus on Lipulekh and Limpiyadhura. Largely concentrated on identifying assorted challenges in resolving Nepal-India border problems, when Nepal faced India with its new map against the latter's new route to Mansarovar, Nepal’s self-help that is limited to diplomatic talks with India has been elaborated along with Indian and Chinese responses to Nepal’s new map and India’s opening of a new route to Mansarovar, respectively. By using Foreign Policy Analysis (FPA) as a tool, this article discusses why diplomatic negotiations haven’t found a headway in the Nepal-India context, despite Nepal's repeated calls. It is a qualitative study that uses data from both primary and secondary sources that include government reports, historical documents, archives, statistics, and treaties. Media sources have also been reviewed to understand various issues of Nepal’s border problems with India. After the coding and familiarisation of the data, analysis and interpretation were done. Highlighting the interconnectedness of the Himalayan geopolitics and India’s securitization of the Himalayan frontier, the article concludes that Nepal’s diplomatic initiative on resolving the border problem has been impacted by power condensation in the Himalaya region and India’s lack of interest.